Composting of empty fruit bunches by microbial inocular - Yeoh, Chui Yen (2010)
The increment of palm oil production increases its by-product wastes such as the empty fruit bunch (EFB) and palm oil mill effluent (POME). To recycle the wastes,large-scale windrow composting system is established. However, the duration of compost production from two months to one-year is not compatible to the daily output of the palm oil mill wastes. Thus, accelerating of EFB composting by using inoculums, urea and a smaller substrate size were investigated. Parameters such as moisture content, temperature, pH, electrical conductivity and turning frequency were used to monitor the composting process of EFB and POME. The carbonnitrogen ratio, UV-vis spectrophotometer test, microorganisms enumeration and germination test were used to assess the maturity of compost. Two pilot scale tests were conducted in an industrial compost plant. The first pilot scale test aims to verify the effectiveness of inoculums and urea addition in 30 tonne of EFB compost piles. Four heaps of EFB with different treatments i.e. addition of 0.03%, 0.3% of commercial inocular, 200 kg urea, and control without any additives were investigated. The result disclosed that the 0.03% of inocular had positively affected the composting performance by decreasing the C/N ratio to 15.04 compared to the control, which had the final C/N of 21.39. The EFB heap with addition of urea also had its C/N decreased to 15.62, thus urea may be a second option for accelerating the composting process. In the second pilot scale trial, four heaps of composts were used. Daily turning was done on a heap containing commercial inocular, a heap added with laboratory inocular consisting 15 types of func ional microbes and the control heap. Another heap with the aboratory inocular was scheduled turning once in every two da ys. This trial revealed that the moisture loss and degradation rate were not significantly different between composts with different turning frequencies. With similar decreasing rate of the C/N ratio and microbes population, the laboratory and commercial inoculars were found similar in assisting composting. Both the inoculars have an enhancing effect on the EFB composting as the C/N of both inoculated composts dropped below 20 at 14 days earlier than control. In the third trial, three composts of 20 kg of EFB each were evaluated for the time efficiency of laboratory inocular in smaller particle size of substrate. Composts with 4 cm and 2 cm particle sizes of EFB were inoculated, and a control with 4 cm fibres was without inocular. The C/N of inoculated composts with 2 cm fibres dropped to 18.31, whereas the control was 20.65. The UV-vis ratio of the 2 cm fibre became constant earlier than the control by at least 3 weeks. Observations on the germination test and microbe enumeration suggested that 2 cm inoculated compost matured earlier, i.e. in 35 days compared to the 4 cm fibre at 49 days and the control not mature even at 60 days. In conclusion, the laboratory inoculars can be useful in speeding up the composting process of EFB, particularly for those with smaller substrate sizes. (499)